Feline Infectious Peritonitis (FIP) in Himalayan Cats at Hasanuddin University Educational Veterinary Clinic: Feline Infectious Peritonitis (FIP) in Himalayan Cats at Hasanuddin University Educational Veterinary Clinic - waode santa monica; Carisma Sumule; Abdul Wahid Jamaluddin; Musdalifah Musdalifah (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2022)
Feline infectious peritonitis (FIP) is a viral disease, this disease can cause death in various types of cats but is not zoonotic. Feline infectious peritonitis (FIP) is caused by Feline corona virus (FCoV) from the family Coronaviridae, genus Alphacoronavirus. The purpose of writing a case study is to find out how to diagnose and treat FIP ​​in cats. Methods for diagnosing FIP include anamnesis, clinical examination, ultrasonographic examination (USG) and laboratory examinations consisting of hematological tests and Rivalta tests. The results of the physical examination showed changes in appetite, diarrhea, weakness, 8% dehydration, Body Condition Score 2, abdominal enlargement. Laboratory results using ultrasound showed accumulation of fluid in the abdominal cavity and kidney enlargement 4.29 cm, while the results of hematological examinations decreased the value of the MCV 33 fL, MCH 12 pg and WBC 1.37 10^3 /uL while the MCHC was 53.7 g/dL has increased, the results of the Rivalta test showed a positive result of FIP found the presence of jellyfish-shaped deposits. Handling of FIP cases is treated with antibiotics, multivitamins, fluid therapy, and feed management.